The Effect Of Giving Purple Sweet Potato And Kepok Banana Talam Cake On Fasting Blood Glucose Levels Of Type 2 Diabetes Mellitus Patients - Anggina Dian Purnama; Retno Wahyuningsih; Ni Ketut Sri Sulendri; Suhaema Suhaema (Jurnal Gizi Prima (Prime Nutrition Journal), 2025)
Background: The number of people with type 2 diabetes mellitus in Indonesia is increasing every year. One of the efforts to manage type 2 diabetes mellitus is providing medical nutrition therapy by consuming foods high in fiber and low glycemic load to control blood glucose levels. Food ingredients with relatively high fiber content and low glycemic index are purple sweet potatoes and kepok bananas as alternative healthy snacks for DM sufferers, namely purple sweet potato talam cake and kepok bananas as high-fiber snacks and low glycemic index.Research Methods: This type of research is a quasi-experimental non-equivalent control group design with a pre-post test and a control group research design. The study's sample size was 38 people selected by systematic random sampling. The samples were divided into two groups, namely the control and treatment groups, by being given purple sweet potato talam cake and kapok banana once a day for seven consecutive days.Research Result: Fasting blood glucose levels before and after the purple sweet potato talam cake and kepok banana study decreased by 35.94 mg/dl in the intervention group and 5.37 mg/dl in the control group.Conclusion: Purple sweet potato talam cake and kapok banana have an effect on fasting blood glucose levels in diabetes mellitus patients, with p = 0.00 (p> 0.05).